Worldwide Analyses of Maxillary First Molar Second Mesiobuccal Prevalence: A Multicenter Cone-beam Computed Tomographic Study - Martins, Jorge N R; Alkhawas, Moataz-Bellah A M; Altaki, Zaher; Bellardini, Gianmarco; Berti, Luiza; Boveda, Carlos; Chaniotis, Antonis; Flynn, Daniel; Gonzalez, Jose Antonio; Kottoor, Jojo; Marques, Miguel Seruca; Monroe, Adam; et al. (Journal of endodontics, 2018)
Maxillary first molar second mesiobuccal (MB2) root canal prevalence may change among different populations. The aim of this study was to analyze the worldwide prevalence of the MB2 root canal and understand its possible relation with sex, age, side, and root configuration using in vivo cone-beam computed tomographic (CBCT) assessment. Observers from 21 regions were calibrated to achieve a similar CBCT assessment methodology and instructed to collect data from 250 maxillary first molars in previously existing examinations. Intra- and interrater reliability tests were performed. The sample size included 5250 molars and was defined by way of a preliminary trial. Data collected included MB2 presence, sex, age, side, number of roots per tooth, and mesiobuccal root configuration. The z test for proportions in independent groups was used to analyze the differences among subgroups. P < .05 was considered significant. The worldwide CBCT-assessed MB2 prevalence was 73.8%, ranging from 48.0% in Venezuela to 97.6% in Belgium. The prevalence in males and females was 76.3% and 71.8%, respectively (P < .05). Significantly higher MB2 proportions were found in younger patients and 3-rooted molar configurations. The group intraclass correlation coefficient and the percentage of agreement for the MB2 presence were 0.95 and 0.91, respectively. The intrarater Cohen kappa value was above 0.61 for all observers. MB2 prevalence in the analyzed regions varied widely. The differences may be associated with specificities within each region but also patient demographics. Males, younger patients, and 3-rooted configurations were associated with higher MB2 proportions.